Uncoupled U/Pb and REE response in zircon during the transformation of eclogite to mafic and intermediate granulite (Blanský les, Bohemian Massif). (12th May 2016) - Štípská, P.; Powell, R.; Hacker, B. R.; Holder, R.; Kylander‐Clark, A. R. C.
ABSTRACT: An eclogite – mafic granulite occurs as a rare boudin within a felsic kyanite – K‐feldspar granulite in a low‐strain zone. Its boundary is marked by significant metasomatism–diffusional gain of potassium at the centimetre‐scale, and probable infiltration of felsic melt on a larger scale. This converted the eclogite – mafic granulite into an intermediate‐composition, ternary‐feldspar‐bearing granulite. Based on inclusions in garnet, the peak P–T conditions of the original eclogite are 18 kbar at 850 – 950 °C, with later matrix re‐equilibration at 12 kbar and 950 °C. Four samples from the transition of the eclogite – mafic granulite through to the intermediate granulite were studied. In the eclogite, REE patterns in the garnet core show no Eu anomaly, compatible with crystallization in the absence of plagioclase and consistent with eclogite facies conditions. Towards the rim of garnet, LREE decrease, and a weak negative Eu anomaly appears, reflecting passage into HP granulite facies conditions with plagioclase present. The rims of garnet next to ternary feldspar in the intermediate granulite show the lowest LREE and deepest Eu anomalies. Zircon from the four samples was analysed by LASS (laser ablation–split‐stream inductively coupled plasma–mass spectrometry). It shows U–Pb ages from 404 ± 4.0 to 331 ± 3.3 Ma, with a peak at 340 ± 4.0 Ma corresponding to the likely exhumation of the rocks to 12 kbar. Older ages from zircon with steep HREE patterns indicate the minimum age of the protolith, and ages <360 ± 4.0 Ma are interpreted to correspond to the eclogite facies metamorphism. Only some zircon grains ≤350 ± 4.0 Ma have flat HREE patterns, suggesting that these are primarily modified protolith grains, rather than new zircon crystallized in the eclogite‐ or granulite facies. The metasomatic processes that converted the eclogite – mafic granulite to an intermediate granulite may have facilitated zircon modification as zircon in the intermediate granulite has flat HREE and ages of 340 ± 4.0 Ma. The difference between the oldest and youngest ages with flat REE patterns indicates a 16 ± 5.6 Ma period of zircon modification in the presence of garnet.